PENGARUH PEMBERIAN TERAPI MUSIK KLASIK DAN MUROTTAL TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER III - Lisca, Shinta Mona; Hermawati, Mila; Br.Ginting, Agus Santi (Bahasa Indonesia, 2024)
Anxiety in pregnant women will increase when the delivery schedule is getting closer, namely entering the third trimester, mothers begin to think about the process of giving birth and the condition of the baby to be born. Mothers who suffer from stress and anxiety during pregnancy in the third trimester will experience an increase in the release of stress hormones, causing disruption of blood flow in the uterus and resulting in weak uterine muscle contractions. This event causes the longer labor process (old partus), the risk of cesarean section, and delivery with tools. The risk to the baby can cause congenital abnormalities in the form of failure to close the palate gap, premature birth, giving birth to babies with low birth weight (BBLR), emergency (fetal stress) and in the long term related to behavioral and emotional disorders of the child. . Based on the results of an assessment of anxiety levels in third trimester pregnant women with Classical Music and Murottal therapy, it is known that during 7-day observation there was a decrease in anxiety levels, namely: 1. There was a decrease in anxiety levels of third trimester2. There was a decrease in anxiety levels of III trimester pregnant women before and after murottal therapy by 26 in 7 days. Based on the results of research on the level of anxiety in III trimester pregnant women, it shows that, pregnant women before and after classical music therapy by 20 in 7 days. There is a difference in reducing the level of anxiety of pregnant women given classical music therapy with murottal therapy. The decrease in anxiety levels of pregnant women who were given murottal therapy was faster than the level of anxiety reduction compared to pregnant women who were given classical music therapy Keywords: : Anxiety for Pregnant Women in the Third Trimester, Classical Music and Murottal Therapy